Urgensi Kurikulum Darurat Covid dalam Pembelajaran Jarak Jauh - Primanita Sholihah Rosmana; Sofyan Iskandar; Nopi Krisnawati; Azzahra Elisa Putri; Fitria Hermawan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The curriculum is an important role in achieving educational goals with various components contained in it. In the existing situations and conditions, the curriculum changes. One of them is the COVID-19 emergency curriculum which is given specifically in a pandemic condition. This research is a descriptive qualitative research which is expected to provide an overview of the importance of the current curriculum. This curriculum is adapted to the distance learning process. Distance learning is a learning process that is carried out face-to-face and there is no direct interaction. Every educator must be able to implement the curriculum that applies to current conditions. With the advancement of technology and the need for changes and improvements, the curriculum is easily implemented in every educational unit. The respondents in this study were given to the general public and became parties who knew the curriculum such as teachers, lecturers and students. Data collection techniques used through e-questionnaire with google form media. From the results of this study, it can be stated that the covid emergency curriculum can be implemented for distance learning with various adjustments made and is expected to provide knowledge and be able to develop for the better.